2018
DOI: 10.1111/nicc.12357
|View full text |Cite
|
Sign up to set email alerts
|

Richards‐Campbell sleep questionnaire: psychometric properties of Chinese critically ill patients

Abstract: If the validity of this questionnaire is supported in other ICU samples, RCSQ-C could be used as a routine evaluation instrument to distinguish good and poor sleepers and then direct nurses to form corresponding treatment plans to promote sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…Interobserver reliability was excellent for the Brazilian Portuguese version of the RCSQ, with an ICC of 0.84. This finding is consistent with those of Chen et al, 24 who found excellent interobserver reliability for the Chinese version of the questionnaire, with an ICC of 0.91. The Farsi version of the RCSQ was found to have good reliability, with an ICC of 0.71.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interobserver reliability was excellent for the Brazilian Portuguese version of the RCSQ, with an ICC of 0.84. This finding is consistent with those of Chen et al, 24 who found excellent interobserver reliability for the Chinese version of the questionnaire, with an ICC of 0.91. The Farsi version of the RCSQ was found to have good reliability, with an ICC of 0.71.…”
Section: Discussionsupporting
confidence: 92%
“…The SICUQ assesses quality of sleep at home, daytime sleepiness, sleep disruption caused by patient care activities, and sleep disruption caused by environmental factors, none of which are assessed by the RCSQ. Studies using this questionnaire 24 , 37 , 38 have shown positive results regarding the implementation of protocols for sleep promotion in the ICU setting and post-ICU evaluation, confirming its utility in clinical practice.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The questionnaire was originally created for critically ill patients and was scientifically validated (Richards et al, 2000). Validity, reliability and internal consistency have been confirmed in several previous studies (Chen et al, 2018;Frisk and Nördstorm, 2013;Nicolás et al, 2008). The RCSQ provides a short, applicable, comprehensive and simple tool to assess sleep quality in ICU and is also the most widespread…”
Section: Introductionmentioning
confidence: 88%
“…Chen et al . () paper presents the translation and application of the Richards‐Campbell Sleep Questionnaire (RCSQ) in China. The RSCQ is a tool used to evaluate a patient's sleep patterns and is widely used in the critical care setting.…”
mentioning
confidence: 99%